β-cell function is regulated by metabolic and epigenetic programming of islet-associated macrophages, involving Axl, Mertk, and TGFβ receptor signaling - Le May Thai; Liam O’Reilly; Saskia Reibe-Pal; Nancy Sue; Holly Holliday; Lewin Small; Carsten Schmitz-Peiffer; Rama Dhenni; Vicky Wang-Wei Tsai; Nicholas Norris; Belinda Yau; Xuan Zhang; et al. (iScience, 2023)
Summary: We have exploited islet-associated macrophages (IAMs) as a model of resident macrophage function, focusing on more physiological conditions than the commonly used extremes of M1 (inflammation) versus M2 (tissue remodeling) polarization. Under steady state, murine IAMs are metabolically poised between aerobic glycolysis and oxidative phosphorylation, and thereby exert a brake on glucose-stimulated insulin secretion (GSIS). This is underpinned by epigenetic remodeling via the metabolically regulated histone demethylase Kdm5a. Conversely, GSIS is enhanced by engaging Axl receptors on IAMs, or by augmenting their oxidation of glucose. Following high-fat feeding, efferocytosis is stimulated in IAMs in conjunction with Mertk and TGFβ receptor signaling. This impairs GSIS and potentially contributes to β-cell failure in pre-diabetes. Thus, IAMs serve as relays in many more settings than currently appreciated, fine-tuning insulin secretion in response to dynamic changes in the external environment. Intervening in this nexus might represent a means of preserving β-cell function during metabolic disease.